Double crossover in the human Xp/Yp pseudoautosomal region and its bearing on interference - Rappold, Gudrun; Klink, Albrecht; Weiß, Birgit; Fischer, Christine (Human molecular genetics, 1994)
Most models on crossover and crossover interference have assumed that the Intensity of interference depends inversely on the physical distance separating the respective intervals. The possibility, however, also exists that Interference depends on genetic rather than on physical distance. As the human pseudoautosomal region (PAR) on Xp/Yp is physically small, yet genetically a hot spot of recombination In male meiosls, studies on the existence of multiple crossover events may be particularly useful In addressing the question of interference. Our results demonstrate for the first time a double crossover during male meiosls In the human PAR on Xp/Yp. The occurrence of a single obligatory recombination event in this region can, therefore, no longer be taken as a dogma. However, double crossover events seem to remain exceptional and, thus, the model originally suggested by Burgoyne remains globally correct. As both recombination events can be localized within a narrow range of physical distance, theories describing interference due to stertc hindrance may have to be reconsidered. This finding may, therefore, have general implications for our understanding of the mechanism of positive and negative crossover Interference In mammalian genomes and may be interesting especially for linkage mapping where double recombinations In small intervals tend to be considered as genotyplng errors.
Gesehen am 31.03.2021